Pengaruh Jumlah Kunjungan Wisatawan Dan Produk Domestik Regional Bruto Penyediaan Akomodasi Dan Makan Minum Terhadap Pendapatan Asli Daerah Di Kabupaten Kutai Kartanegara (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
Ani 2019. The Influence of the Number of Tourist Visits and Gross Regional Domestic Product in the Provision of Accommodation and Food and Beverage Sector to the Original Regional Adaptation in the District of Kutai Kartanegara. Supervised by Priyagus as Advisor I and Erwin Kurniawan A as Advisor II.This study aims to determine the effect of the number of domestic tourist visits, the number of foreign tourist arrivals and the GRDP of the accommodation and food and beverage supply sector to the original revenue of the district of Kutai Kartanegara. The data used in this research is secondary data. The method used is multiple linear regression with the SPSS 22 program.The results showed that the number of domestic tourist visits had a negative and significant relationship to the original income of the region, the number of foreign tourist visits had a negative and not significant effect on the regional authentic income and the GRDP of the accommodation and eating and drinking supply sector had a positive and significant relationship to the original income of the Kutai Regency Kartannegara.